Intraoperative radiotherapy for pancreatic cancer: implementation and initial experience. Issue 12 (29th September 2021) - Bhome, R; Karavias, D; Armstrong, T; Hamady, Z; Arshad, A; Primrose, J; Bateman, A; Pearce, N; Takhar, A
Abstract : This article reports on the first series of patients to receive intraoperative radiotherapy for pancreatic cancer in the UK. The data suggest that this treatment modality is feasible and safe, laying a platform for collaborative multicentre trials to better assess efficacy.